New Knowledge in Information Systems and Technologies Volume 2 - Rocha, Álvaro; Adeli, Hojjat; Reis, Luís Paulo; Costanzo, Sandra; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book includes a selection of articles from The 2019 World Conference on Information Systems and Technologies (WorldCIST'19), held from April 16 to 19, at La Toja, Spain. WorldCIST is a global forum for researchers and practitioners to present and discuss recent results and innovations, current trends, professional experiences and challenges in modern information systems and technologies research, together with their technological development and applications. The book covers a number of topics, including A) Information and Knowledge Management; B) Organizational Models and Information Systems; C) Software and Systems Modeling; D) Software Systems, Architectures, Applications and Tools; E) Multimedia Systems and Applications; F) Computer Networks, Mobility and Pervasive Systems; G) Intelligent and Decision Support Systems; H) Big Data Analytics and Applications; I) Human-Computer Interaction; J) Ethics, Computers & Security; K) Health Informatics; L) Information Technologies in Education; M) Information Technologies in Radiocommunications; and N) Technologies for Biomedical Applications.
Multi-Agent Neural Reinforcement-Learning System with Communication -- Technological Architecture based on Internet of Things to Monitor the Journeys of Artisanal Fishing -- Gesture Based Alternative To Control Recreational UAV -- Automatic Generation of a Sub-optimal Agent Population with Learning -- App Nutrition Label -- Yet Another Virtual Butler to Bridge the Gap Between Users and Ambient Assisted Living -- Usage of HTTPS by Municipal Websites in Portugal -- Cybersecurity Threats Analysis for Airports -- Player Engagement Enhancement with Video Games -- Web-Based Executive Dashboard -- Standardization Issues for the Internet of Things -- An Efficient Sybil Attack Detection for Internet of Things -- Flow Monitoring System for IoT Networks -- Real Time Fuzzy Based Traffic Flow Estimation & Analysis -- Optimized Community Detection in Social Networks -- Usability Evaluation of a Virtual Assistive Companion -- Privacy Preserving kNN Spatial Query with Voronoi Neighbors -- Analysis of Authentication Failures in the Enterprise.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence